Translational Research in Stem Cell Treatment of Neuromuscular Diseases. (5th November 2012) - Orbay, Hakan; Mizuno, Hiroshi
Abstract : Neuromuscular diseases are a heterogeneous group of diseases that lead to significant disability in effected individuals. Pharmacological treatments failed to provide any significant improvement to date. Recently, the introduction of stem cells into the field of health sciences raised the hopes for a new treatment for neuromuscular diseases. In theory, stem cells, owing to their multilineage differentiation capacity, could differentiate into myofibers and neurons and replace the degenerated cells leading to recovery of the patients. Results obtained from the preclinical studies supported this theory. However, clinical trials with stem cells could not meet the expectations mainly because of early mortality, limited migration, and differentiation of the implanted cells. Modification of the stem cells before implantation, such as introduction of deficient genes or commitment to a precursor cell line provided little improvement. The biggest barrier to overcome for a successful of stem cell treatment, which also should be the focus of the future studies, is to increase the functional integration of the donor cells with the recipient tissues. Understanding the underlying pathogenic mechanisms of the neuromuscular diseases is essential to achieve this goal.